A114: Methylprednisolone‐Induced Inhibition of miR‐155 Expression Increases SOCS1‐Driven Suppression of Cytokine Signaling. Issue 11 (March 2014) - Davis, Trevor E.; Kis‐Toth, Katalin; Tsokos, George C.
Abstract : Background/Purpose: MicroRNA (miRNA, miR) are short RNA species (20–23 nt) that act post‐transcriptionally modulating messenger RNA (mRNA) translation or stability. They control many biological processes including cell differentiation and homeostasis. Abnormal levels of miRNA have been implicated in cancers and autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus. Steroids are first line anti‐inflammatory medications that act through transcriptional or posttranscriptional gene regulation. In multiple instances steroids cause mRNA destabilization indicating a potential role for miRNA. Previously, using high‐throughput microarray analysis, we found that methylprednisolone (MP) decreased miR‐155 expression in CD4 + T cells in vitro . miR‐155 is highly expressed in immune cells and influential in cell differentiation. This influence may in part be mediated through suppression of cytokine signaling 1 (SOCS1), a known target of miR‐155. SOCS1 inhibits multiple JAK/STAT pathways, which may inhibit cell proliferation and differentiation. Steroids have also been shown to inhibit proliferation, differentiation and the JAK/STAT pathways. Steroids through blocking the IL‐12/STAT4 pathway inhibit Th1 differentiation. This pathway is in part controlled by SOCS1, which should be under the control of miR‐155. Following our previous work here we explore the potential mechanism of action of miR‐155 during MP treatment of T cells. Methods: Total or naive CD4 + T cells were isolated from peripheral blood of healthy donors and activated by anti‐CD3/anti‐CD28 antibodies for up to 5 days with or without Th1 polarizing conditions (10 nM IL‐12 and 5 mM anti‐IL‐4 neutralizing antibody) and with or without exposure to 10 −6 M of methylprednisolone. Some cells were first transfected with mimic miR‐155, control mimic miR, anti‐miR‐155, or control anti‐miR by electroporation. Effects on miR‐155, SOCS1, STAT phosphorylation, IFNg production and Th1 differentiation were monitored using flow cytometry, RNA quantification by PCR, and protein quantification by ELISA or western blot analysis. Results: Activated T cells treated with MP decrease miR‐155 expression and increase SOCS1 expression. In turn, SOCS1 decreases JAK/STAT signaling and inhibits response to cytokines, notably IL‐12, resulting in decreased IFNg production by activated T cells. Conclusion: We found that the anti‐inflammatory effects of MP, at least in part, act through decreasing miR‐155 in T cells by inhibiting JAK/STAT signaling and cytokine production through modulating SOCS1 expression. Based on our findings we propose that miR‐155 inhibition could be utilized to suppress inflammation without the myriad of side effects currently inherent in chronic steroid therapy.